2020
DOI: 10.2139/ssrn.3551767
|View full text |Cite
|
Sign up to set email alerts
|

High Temperature and High Humidity Reduce the Transmission of COVID-19

Abstract: This paper investigates the influence of air temperature and relative humidity on the transmission of COVID-19. After estimating the serial interval of COVID-19 from 105 hand-collected pairs of the virus carrier and the infected, we calculate the daily effective reproductive number, R, for each of all 100 Chinese cities with more than 40 cases. Using the daily R values from January 21 to 23, 2020 as proxies of nonintervened transmission intensity, we find, under a linear regression framework, high temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

70
609
17
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 595 publications
(718 citation statements)
references
References 32 publications
70
609
17
10
Order By: Relevance
“…Although some evidence suggests that warmer weather may slow the spread of the virus [88], the WHO continues to recommend the following of all official guidelines. It is still too early to know how SARS-CoV-2 interacts with hot weather but the spread of other coronaviruses were slowed in warmer environments.…”
Section: Guidelines To Prevent the Spread Of Sars-cov-2 Infectionmentioning
confidence: 99%
“…Although some evidence suggests that warmer weather may slow the spread of the virus [88], the WHO continues to recommend the following of all official guidelines. It is still too early to know how SARS-CoV-2 interacts with hot weather but the spread of other coronaviruses were slowed in warmer environments.…”
Section: Guidelines To Prevent the Spread Of Sars-cov-2 Infectionmentioning
confidence: 99%
“…A previous study in the four major Chinese cities suggested that the SARS outbreak was significantly associated with the temperature, increasing the daily incidence rate with lower temperatures (Tan et al, 2005). Recent preprint studies using national data from countries affected by COVID-19 reported that low temperature is beneficial to the viral transmission (Triplett 2020;Wang et al, 2020a;Wang et al, 2020b). However, these should be taken with caution since have not yet been peer reviewed.…”
Section: Dear Editormentioning
confidence: 99%
“…It is really important to find out all the factors that play a role in COVID-19 spreading in Urban. The transmission of viruses can be affected by many factors, including climate conditions (such as temperature and humidity), population density and medical care quality (Wang et al, 2020). Therefore, understanding the relationship between the geographical features of a country and the transmission of COVID-19 is key to making the best decision to control and prevent the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the discipline of geography is playing in the fight against the virus SARS-CoV-2, which causes coronavirus disease . Therefore, urban geography can be very helpful in that the spatial organization of the city determines the spatial pattern of the spread of the disease (Boulos and Geraghty, 2020;Wang et al, 2020). While a set of health experts are banking on warmer weather conditions to slow down, if not completely halt, the Coronavirus, it is yet not clear whether the coming months will bring any respite to the world.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation